Harmonic Meter Design Using Arduino - Rizki Lubis, Azmi; Antoni, A; Harahap, Bonar; Tarigan, Gunawan; Sarifah, Jupriah (International Journal of Engineering and Technology, 2018)
This paper discusses the measurement of harmonic content using arduino which is simulated with proteus software. The components used in this meter harmonic circuit are resistor, capacitor, LCD, microcontroller atmega 328P. Microcontroller works based on voltage source (TR1) and current source (TR2) on proteus software. The voltage and current delivered to the microcontroller will be read and executed according to the program on the microcontroller. The program used in this arduino microcontroller is the C language program. The results obtained from this study Arduino successfully measure the harmonic content and display the measurement results on the LCD.Â Â